2014
DOI: 10.1088/1748-0221/9/10/p10007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of NEXT-DEMO using xenon KαX-rays

Abstract: The NEXT experiment aims to observe the neutrinoless double beta decay of 136 Xe in a high-pressure xenon gas TPC using electroluminescence (EL) to amplify the signal from ionization. Understanding the response of the detector is imperative in achieving a consistent and well understood energy measurement. The abundance of xenon K-shell X-ray emission during data taking has been identified as a multitool for the characterisation of the fundamental parameters of the gas as well as the equalisation of the respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
3
36
1
Order By: Relevance
“…This detector, named NEXT-100, possesses two features of great value for 0νββ-decay searches: excellent energy resolution (<1% FWHM at 2.5 MeV) [12,13] and charged-particle tracking for the active suppression of background [14,15]. Furthermore, the technology can be extrapolated to large source masses, thus allowing the full exploration of the inverted-hierarchy region of neutrino masses.…”
Section: Jhep05(2016)159mentioning
confidence: 99%
See 2 more Smart Citations
“…This detector, named NEXT-100, possesses two features of great value for 0νββ-decay searches: excellent energy resolution (<1% FWHM at 2.5 MeV) [12,13] and charged-particle tracking for the active suppression of background [14,15]. Furthermore, the technology can be extrapolated to large source masses, thus allowing the full exploration of the inverted-hierarchy region of neutrino masses.…”
Section: Jhep05(2016)159mentioning
confidence: 99%
“…An energy resolution of 1% FWHM at 662 keV, which -assuming a 1/ √ E dependence -extrapolates to 0.5% FWHM at the Q value of 136 Xe, was measured in the DBDM prototype [12]. The best resolution measured in DEMO, 1.62% FWHM at 511 keV, extrapolates to 0.74% FWHM [13]. In addition, the NEXT-DEMO prototype has shown that track reconstruction is possible with an EL-based amplification scheme [14] and that the reconstructed energydeposition pattern can be used for the identification of signal-like and background-like event topologies [15].…”
Section: Jhep05(2016)159mentioning
confidence: 99%
See 1 more Smart Citation
“…The NEXT detector concept provides excellent energy resolution, close to 0.5% at the Q value of 136 Xe [5,6]. The unique trace left in the detector by the decay makes track reconstruction an additional powerful handle to reject background [7].…”
Section: Energy Plane (Pmts)mentioning
confidence: 99%
“…The energy resolution was measured with both detectors. In NEXT-DEMO, the 0.511 MeV 22 Na photopeak was reconstructed at 1.62% FWHM [2], while a resolution of 1.00% FWHM was achieved for the 0.662 MeV 137 Cs peak [3] in NEXT-DBDM (see Fig. 2).…”
Section: Next-demo and Next-dbdmmentioning
confidence: 99%